Ngumbai Lawok Ceremony: Social Construction and 'Urf' Perspective of the Coastal Muslim Community of Lampung - Anwar, Muhammad Saidun; Izomiddin, Izomiddin; Rochmiatun, Endang; Noupal, Muhammad; Choirudin, Choirudin (UIN Sunan Gunung Djati Bandung, 2022)
The study aims to explain the process of externalization, objectification, and internalization in the urf study of the implementation of ngumbai lawok. The research uses an ethnographic approach where data is taken by looking directly at the ceremonies and traditions to obtain details of the implementation carried out. Analysis of the data used is a descriptive analysis technique by describing the object's state under study. The results of this study describe ngumbai lawok is a form of traditional ceremony celebrated or carried out by the people of the West Coast as a form of gratitude to Allah swt to get fruitful results and avoid the calamity that will occur. The externalization process creates the ngumbai lawok ceremony, which is obtained based on his beliefs so far. The objectification process, which includes the ngumbai lawok ceremony, is obtained from the externalization process. Institutional agents consist of traditional leaders, community leaders, village heads, and fishing communities. The internalization process is explored in the name of the community again, perceiving and interpreting every meaning of the ngumbai lawok ceremony. Based on the urf theory review, ngumbai lawok is a form of gratitude in God's nature. In addition, it is a custom that has been accepted by the wider community, justified by considerations of common sense, brings good, and rejects damage. In ngumbai lawok, the request is also purely addressed to Allah and hopes for the blessing and salvation. In addition, in the ngumbai lawok ritual, in essence, the Coastal community only respects their previous ancestors and carries out traditions from generation to generation.